Experimental and numerical investigation of heat transfer and flow characteristics for tractor heat exchanger (radiator) - Nasir, Kadhim F. (Nahrain University College of Engineering Journal, 2017)
An experimental and numerical study was carriedout to investigate heat transfer and flowcharacteristics through the tractor heat exchanger(radiator). The engine of the tractor is Diesel(compression ignition) engine type. Theexperimental study used heat exchanger (radiator)manufactured from copper instead of the originalheat exchanger of the tractor, which ismanufactured from iron. Both heat exchangersconsist of circular cross sectional tubes and platefins. The temperatures was measured inside thecooling room of engine for both cases at the sametime and the same loads. The results of theexperimental investigation showed that the heatexchanger is manufactured from copper providedtemperatures less than the heat exchangermanufactured from iron, that means heat rejectedby copper heat exchanger is more than heatrejected by iron heat exchanger. The use of copperheat exchanger is better than iron heat exchangerfor cooling the tractor engine. In the numericalstudy used model of copper heat exchanger toanalyzed by CFD method at different air velocityfrom (0.5 m/sec) to (7 m/sec) for laminar air flow.The object of this study was enhancement the heattransfer process from the cooling fluid of heatexchanger. The results of the numerical studyshows that heat transfer rate increase withincreasing air flow during heat exchanger(radiator). Good agreement between experimentaland numerical results is obtained.